Reaction time and efficiency of the goalball player in interception/ defense of throwing/attack - Gilberto Pereira da Silva; Vanildo Rodrigues Pereira; Pedro Paulo Deprá; José Irineu Gorla (Desafio Singular, 2010)
Goalball is a team sport designed for the blind and the visually impaired. This research aimed at analyzing the motor behavior of goalball players in order to evaluate the influence of reaction time (TR) in the efficiency of defense actions. Nine athletes from the national team of goalball, who played in the 3rd World Games of IBSA (São Caetano do Sul/SP, August 2007), participated in this study. Data were collected through cinemetry in order to obtain images of motor movements during defense actions and then analyzed and developed using the biomechanics model of motor control of human movements, and treated using a software specific for analyzing movement, the DgeeMe Version 1.0b. Participants' TR met the standard mentioned in the literature. Repetition of movements and promptness to act influenced the quality of their responses and facilitated a decrease in TR.